Procedural Acceleration and Judicial Procedure in Eletronic Media: Case Study at the Court of the State of São Paulo - Ribeiro Rotta, Maurício José (2013)
This article discusses the average time of trial processes in both physical and digital media, from the Brazilian State Courts of Justice, and the results obtained by the implementation of the digital judicial process in these Courts. Therefore, a literature review on digital judicial process was performed, and quantitative and qualitative analysis of time series data and information obtained from the National Council of Justice - Justice in Numbers, in the years 2009, 2010 and 2011, from the Brazilian State Courts of Justice. As a result, it was possible to verify the occurrence of very large variation between the time of the filing of cases in trial and its transit to the same class processes into courts of equal competence, in the same period. By analyzing more carefully those courts where best practices related to digital process are employed, where there is use of electronic management system of lawsuits, and a staff of clerks and magistrates well scaled with respect to work load, the results are very positive, demonstrating the procedural acceleration in digital media can be three to four times faster than in the physical media.